Lipoprotein Associated Phospholipase A2 Activity and Itâs Additive Value inCardiovascular Risk Stratification - W, Andi; C, Miryanti; R, Saifur; H, Dadang; ., Widodo (UNEJ e-Proceeding, 2014)
Background: Lipoprotein associated phospholipase A2Â  (Lp-PLA2) has been known as a usefulÂ  inflammatory marker of cardiovascularÂ  risk. FraminghamÂ  scoreÂ  hasÂ  alsoÂ  been widelyÂ  usedÂ  inÂ  longÂ  termÂ  cardiovascularÂ  riskÂ  stratification.Â  However,Â  itÂ  remainÂ  toÂ  be clarified whether increased Lp-PLA2 activity and Framingham score significantly increase odd ratio (OR) in acute myocardial infarction (AMI) setting. We therefore investigated Lp- PLA2 activityÂ  andÂ  itâsÂ  additiveÂ  valueÂ  forÂ  FraminghamÂ  cardiovascularÂ  riskÂ  among myocardial infarction men.Blood samples were drawn from 60 men admitted to intensive care unit early after myocardial infarction and 40 healthy men with negative treadmill test as a control. Framingham score were calculated among all subjects. We measured Lp-PLA2 activity by ELISA. Lp-PLA2Â  activity was significantly higher in patients with myocardial infarction than those in controlÂ  (83.97Â±27.15Â  nmol/ml/minuteÂ  vs.Â  57.48Â±32.30Â  nmol/ml/minute; p=0.000). ROC analysis was performed to identify the most useful Lp-PLA2 cut-off level. Lp-PLA2 activity equal to or more than 74.21Â  nmol/ml/minute associated with myocardial infarction with accuracy 68%. The OR of AMI was increased by Lp-PLA2Â  activity added to Framingham score from 0.89(CI 95% 0.38- 2.11) to 4.48(CI 95% 1.90- 10.56) Conclusion:Â  AdditionÂ  ofÂ  Lp-PLA2Â Â  activityÂ  toÂ  FraminghamÂ  scoreÂ  mayÂ  hasÂ  additive predictive value in cardiovascular risk stratification. Keywords: Lp-PLA2, myocardial infarction, cardiovascular risk stratification